Keihäänheittäjien katsekäyttäytyminen heittosuorituksen aikana - Reunanen, Sami (2024)
The purpose of this study was to investigate potential differences in gaze behavior between elite and intermediate level javelin throwers. The focus was on variables used in meta-analyses of the topic, which include Quiet eye durations, gaze direction, and the number of fixations between transitions and the pulling phase. Gaze behavior has been strongly suggested as an explanatory factor for performance differences in previous literature. Quiet eye refers to gaze control, defined as the final fixation or eye movement before action initiation. Longer Quiet eye durations allow for more detailed processing of motor programs and the required cortical organization. This study aims to address the following questions: What is the gaze behavior of javelin throwers? What potential differences exist in gaze behavior between elite and intermediate throwers? The study involved four elite and seven intermediate javelin throwers. Data collection and measurements were conducted using eye-tracking glasses during throwing exercises at indoor facilities across Finland. Results showed that measurements of elite throwers were significantly better in terms of Quiet eye durations and gaze direction compared to intermediate throwers. The number of fixations did not show statistically significant evidence. Elite throwers had, on average, half the duration of Quiet eye compared to intermediate throwers. Elite throwers also exhibited a more focused gaze anchor during the throwing performance compared to intermediate throwers. The results indicate that differences in gaze behavior between elite and intermediate throwers support previous literature. Based on the study, it can be concluded that long Quiet eye durations and a clearly focused gaze are also significant factors explaining performance differences among javelin throwers. In the future, javelin training should incorporate methods of Quiet Eye training and other gaze control exercises to more effectively develop intermediate-level throwers towards achieving SM-level results.